2018
DOI: 10.1038/s41598-018-32065-2
|View full text |Cite
|
Sign up to set email alerts
|

Increased Phosphaturia Accelerates The Decline in Renal Function: A Search for Mechanisms

Abstract: In chronic kidney disease (CKD), high serum phosphate concentration is associated with cardiovascular disease and deterioration in renal function. In early CKD, the serum phosphate concentration is normal due to increased fractional excretion of phosphate. Our premise was that high phosphate intake even in patients with early CKD would result in an excessive load of phosphate causing tubular injury and accelerating renal function deterioration. In CKD 2–3 patients, we evaluated whether increased phosphaturia a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 22 publications
3
40
0
1
Order By: Relevance
“…These data indicate that, although phosphate metabolism is dysregulated in our model, serum phosphate levels were kept constant through increased renal phosphate excretion. Given the evidence that chronic kidney injury and phosphaturia can alter full-length, renal Klotho expression levels 29,31 , we evaluated Klotho abundance. We found that the renal Klotho levels were lower in the DSH group than in the DSN group and that these changes were alleviated by SF ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These data indicate that, although phosphate metabolism is dysregulated in our model, serum phosphate levels were kept constant through increased renal phosphate excretion. Given the evidence that chronic kidney injury and phosphaturia can alter full-length, renal Klotho expression levels 29,31 , we evaluated Klotho abundance. We found that the renal Klotho levels were lower in the DSH group than in the DSN group and that these changes were alleviated by SF ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…FGF23 stimulates pro-fibrotic and pro-hypertrophic factors in cardiomyocytes and induces fibrosis-related pathways in fibroblasts [55,59,60]. In addition to its direct effects on cardiac remodeling, FGF23 has also been shown to increase blood pressure [61], inflammation [62] and CKD progression itself [63], and may thus promote the development of LVH also by indirect mechanisms. FGF23 signaling in the liver causes production of inflammatory cytokines.…”
Section: Fgf23mentioning
confidence: 99%
“…Thus, adequate nutritional intake of P is essential for healthy life. However, the deleterious consequences of increased P intake are also well known, especially in patients with reduced renal function [ 11 ]. Western diets are typically rich in P and the use of P as a food additive further increases the P content of many processed foods.…”
Section: Introductionmentioning
confidence: 99%